Notes on the Diet of Gerres Macracanthus Bleeker, 1854 (Pisces: Gerreidae) - Dollar, Ma. Louella L. (Silliman Journal, 2024)
The food of Gerres macracanthus Bleeker, 1854 from inshore waters near Townsville, North Queensland, Australia, was studied from April 1984 to April 1985. Analysis of gastrointestinal contents revealed G. Macracanthus to be a carnivore, feeding mainly on benthic invertebrates, particularly polychaetes. Molluscs, e.g. gastropods and bivalves, microcrustaceans and detrital materials make up the rest of the diet.